2007
DOI: 10.1227/01.neu.0000255522.42579.ea
|View full text |Cite|
|
Sign up to set email alerts
|

Spinal Cord Stimulation versus Reoperation for Failed Back Surgery Syndrome: A Cost Effectiveness and Cost Utility Analysis Based on a Randomized, Controlled Trial

Abstract: SCS was less expensive and more effective than reoperation in selected failed back-surgery syndrome patients, and should be the initial therapy of choice. SCS is most cost-effective when patients forego repeat operation. Should SCS fail, reoperation is unlikely to succeed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
185
0
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(193 citation statements)
references
References 28 publications
1
185
0
7
Order By: Relevance
“…18 Levy and coworkers 13 performed a nationwide study on neurological complications after using surgical paddles for SCS across all indications; the study involved about 44,857 patients. The rare complication for a spinal epidural hematoma (EDH) was observed in 0.19% of patients, two-thirds of whom exhibited substantial motor deficit.…”
Section: Discussionmentioning
confidence: 99%
“…18 Levy and coworkers 13 performed a nationwide study on neurological complications after using surgical paddles for SCS across all indications; the study involved about 44,857 patients. The rare complication for a spinal epidural hematoma (EDH) was observed in 0.19% of patients, two-thirds of whom exhibited substantial motor deficit.…”
Section: Discussionmentioning
confidence: 99%
“…In a third-party review of the first 42 patients in a separate, randomized, controlled, crossover trial comparing SCS with reoperation in patients with failed back surgery syndrome, North et al 20 concluded that SCS was ''less expensive and more effective than reoperation in selected patients and should be the initial therapy of choice. ' …”
Section: A Systematic Review Concluded That There Is Level Ii-1 or IImentioning
confidence: 99%
“…The therapy has been demonstrated to be more effective than repeat back surgery and medication management in the control of pain [18,19]. Traditional or tonic stimulation has been used since the 1960s and is a widely accepted approach to managing neuropathic pains.…”
Section: Spinal Cord Stimulationmentioning
confidence: 99%